Sosialisasi Pentingnya Perilaku Bersih dan Hidup Sehat (PHBS) - Andi Niartiningsih; Nurul Hidayah Nur; Nurfitriani; Mene Paradilla (Jurnal Inovasi Pengabdian Masyarakat, 2025)
Community service aims to provide an understanding of clean and healthy living behavior to the community. Through socialization that has been carried out well, participants are given knowledge about the steps for healthy living so that personal awareness is formed, the family and all its members are able to help themselves in the health sector and have an active role in community activities. Interactive and participatory counseling methods are used to invite participants to be actively involved in learning. Before the socialization, participants filled out a questionnaire to measure their understanding and attitudes regarding clean living. The results of the questionnaire are the basis for an initial evaluation to determine the level of knowledge and awareness of participants before socialization is carried out. After socialization, participants were asked to fill out the same questionnaire to evaluate changes in their understanding, attitude and readiness towards clean living. The evaluation results showed a significant increase in participants' understanding of the steps for living a life that maintains cleanliness and meets health standards. This evaluation provides an indication that the PHBS socialization has had a positive impact on participants in increasing their awareness and preparedness for fires. As a further step, it is necessary to carry out regular monitoring and evaluation to ensure the continuity of the understanding and attitudes that have been improved by participants. Collaboration with related parties such as village or sub-district officials and health services can also strengthen efforts to improve the level of public health.